Biological Activities of Tetrahydroisoquinolines Derivatives - Jordaan, Maryam A.; Ebenezer, Oluwakemi (Z͡h︡urnal orhanichnoï ta farmat͡s︡evtychnoï khimiï, 2023)
1,2,3,4-Tetrahydroisoquinoline (THIQ) is a common scaffold of many alkaloids isolated from several plants and mammalian species. THIQ derivatives possess a broad spectrum of biological activities, including antitumor, antitubercular, antitrypanosomal, antibacterial, anti-HIV, anti-inflammatory, anti-Alzheimer, and anticonvulsant ones.Aim. To cover updated studies on the biological properties of THIQ derivatives, as well as their structure-activity relationship (SAR), in order to highlight the effect of diverse functional groups responsible for the manifestation of the desired activity.Results and discussion. We have presented the review on biological activities of THIQ. The SAR studies show that the electron-donating, electron-withdrawing and some heterocyclic functional groups on the backbone plays a vital role in modulating the biological potential of the compounds synthesized.Conclusions. This review will help pharmaceutical researchers to synthesize novel and potent compounds containing THIQ scaffold. 1,2,3,4-Тетрагідроізохінолін (ТГІХ) є розповсюдженим каркасом багатьох алкалоїдів, виділених з кількох видів рослин і ссавців. Похідні ТГІХ мають широкий спектр біологічних активностей, зокрема протипухлинну, протитуберкульозну, протитрипаносомну, антибактеріальну, анти-ВІЛ, протизапальну, протисудомну дію, а також є перспективними агентами для лікування хвороби Альцгеймера.Мета. Цей огляд охоплює оновлені дослідження з біологічних властивостей похідних ТГІХ, а також взаємозв’язок між їхньою структурою та активністю (SAR), щоб підкреслити вплив різноманітних функціональних груп, відповідальних за прояв бажаної активності.Результати та їх обговорення. У роботі наведено огляд біологічної активності ТГІХ. SAR дослідження свідчать, що електронодонорні, електроноакцепторні та деякі гетероциклічні функціональні групи, зв’язані з каркасом ТГІХ, відіграють дуже важливу роль у модулюванні біологічного потенціалу синтезованих сполук.Висновки. Цей огляд допоможе дослідникам у галузі фармацевтики синтезувати нові та ефективні сполуки, що містять базову структуру ТГІХ.